Broad analysis of serum and intrathecal antimicrobial antibodies in multiple sclerosis underscores unique role of Epstein-Barr Virus - Pache, Florence; Otto, Carolin; Wilken, Diana; Lietzow, Tatjana; Steinhagen, Katja; Grage-Griebenow, Evelin; Schindler, Patrick; Niederschweiberer, Moritz; Wildemann, Brigitte; Jarius, Sven; Ruprecht, Klemens (Neurology: Neuroimmunology & Neuroinflammation ; official journal of the American Academy of Neurology, 2025)
Background and Objectives - There is a strong link between Epstein-Barr virus (EBV) and multiple sclerosis (MS), but the underlying mechanisms are unclear. Patients with MS typically have a polyspecific intrathecal production of immunoglobulin G (IgG), part of which is directed against various microbial antigens. In this study, we comprehensively analyzed seroprevalences and frequencies of an intrathecal IgG production to EBV compared with 10 other common microbes in patients with MS. - Methods - Antibodies to EBV and to Borrelia burgdorferi, cytomegalovirus, herpes simplex virus type 1/2, measles virus, mumps virus, rubella virus, parvovirus B19, tick-borne encephalitis virus, Toxoplasma gondii, and varicella zoster virus (VZV) were determined in stored paired CSF and serum samples of 50 patients with MS. Intrathecal antimicrobial antibody production was assessed by calculating antibody indices (AIs) according to standard formula. - Results - While 50 (100%) of 50 patients with MS were EBV seropositive, seroprevalences of all other 10 microbes were lower, ranging from 94% (VZV) to 6% (Borrelia burgdorferi). An intrathecal production of antimicrobial antibodies was detected in 102 (28%) of 370 AI determinations of patients who were seropositive to the respective antimicrobial antibodies but was practically absent in seronegative patients (2/187 [1%], p < 0.0001). The frequency of intrathecally produced antimicrobial antibodies among patients who were seropositive for the respective antibodies was roughly 40% for measles, rubella, mumps, and VZV and 70% for parvovirus B19. By contrast, the frequency of intrathecally produced EBV antibodies was low (10%) and, when related to their respective seroprevalences, lower than those of all other investigated microbes. - Discussion - Despite the universal EBV seroprevalence, the frequency of intrathecally produced EBV antibodies in patients with MS is lower than that of other microbes, whose seroprevalences are lower than those of EBV. This seemingly paradoxical finding underscores the unique role of EBV in MS and could be explained by the hypothesis that B lineage cells responsible for intrathecal antibody production are primed during and through acute EBV infection to enter the CNS of patients with MS, that is, at a time point when EBV antibody-producing cells have not yet been generated and, therefore, are not yet available for entering the CNS.
Online verfügbar: 27. November 2024, Artikelversion:
Gesehen am 09.07.2025